KEBIJAKAN KELAUTAN DALAM KERANGKA MENJAGA DAN MENGELOLA SUMBER DAYA ALAM LAUT - Nany Suryawati (Legality : Jurnal Ilmiah Hukum, 2016)
By not described the 1982 UNCLOS in detail yet on a legislation, give rise to conflicts of authority in the management of natural resources, particularly coastal and marine resources. With the enactment of Law No. 32 of 2004 on Regional Government, the central Government gives greater authority to local governments to be able to manage coastal and marine resources, as well as regulate the central and local financial balance from the proceeds of natural resource management in the region. With this expected welfare of the local community can be increased significantly. The amount of authority given to the local government not expected to pose an excessive sense of regionalism that could harm the unity of the Republic of Indonesia. Therefore we need a thought which is based on national interest and progress of the nation and the state, through law enforcement and legislation and specific policies in anticipation of a conflict of interest and the use of illegal conducted by both Indonesian citizens and foreign citizens, which may be detrimental to the Unitary Republic of Indonesia.